Report on the practice-in-industry training in fish culture. - Bongco, Angelita; Alfonso R. Sebastian (1963.)
Fish culture and fishing are examples of science activities. For "Science is concerned with the investigation of nature, the accumulation of factual knowledge about the universe and particularly with the formulation of laws in an attempt to explain the relationship between the natural phenomena". Although science is not essentially devoted to practical ends, the understanding of nature which may be gained by the processes of science has found a great application to human activities. It is likely that the current lack of science in fisheries is an indication of the scope that awaits its application, and the next few decades may well see a great expansion in fishery activities that are rationally based on scientific knowledge. This is likely to be apparent particularly in inland fisheries. The application of general scientific fisheries principles demands experimentation on a pilot scale. In marine fisheries, it is particularly difficult to try out a new idea when part of an ocean and large fleet of vessels belonging to several nations, maybe involved. Most inland fisheries, however, are broken into a large number of small units, and new ideas can thus be tried out in one or two lakes or fish farms before being generally introduced. In the ensuing text it will be assumed that it is usually the aim of fishery management to produce the maximum sustained number of catch of fish. Discussed and described herein are the most modern scientific techniques of fish farming in the demonstration fish farms of Pangasinan province.
Report (Undergraduate, Fish Capture) College of Fisheries, University of the Philippines, Manila. 1963.
Keywords: Fish -- culture